Feminist Companion to the Song of Songs. - Brenner, Athalya (Feminist companion to the Bible., 1993)
This volume is the first in a series which provides a fundamental resource for feminist biblical scholarship, containing a comprehensive selection of essays, both reprinted and specially written for the series, by leading feminist scholars.